STUDY ON THE ASSOCIATION BETWEEN THE SEVERITY OF CHRONIC PERIODONTITIS AND CAROTID ATHEROSCLEROSIS - Ovidiu Nicolaiciuc; Irina Georgeta Sufaru; Ioana Sioustis; Liliana Pasarin; Zenovia Surlari; Stefan Luchian; Delia Nicolaiciuc; Tiberiu Tirca; Ciprian Rezus; Silvia Martu (Romanian Society of Oral Rehabilitation, 2018)
Introduction and aim of the study: The aim of this study was to evaluate whether there is a correlation between the severity of chronic periodontitis and atherosclerosis, quantified by intima-media thickness (IMT). Materials and method: Fifty adult patients who received consecutive duplex carotid scans in the lab were included. The study included patients diagnosed with atherosclerosis and healthy patients. The following periodontal clinical variables were evaluated: plaque index; bleeding on probing; probing depth (PD); gingival recession; the level of clinical attachment (CAL). Results: Regarding the magnitude of PD, most sites were found in the test group: 33.9% for IMT> 1 mm without plaque and 47.1% for the atheroma group; differences were statistically significant between groups (p <0.05). The atheroma plaque group revealed 11.8% of subjects with mild periodontitis, 17.6% moderate periodontitis and 70.6% severe periodontitis. In patients with a history of stroke, more severe forms of periodontitis were associated with an increase in IMT and atheroma plaques (p<0.001). Discussions: Approximately 70% of patients with atheroma plaque experienced severe periodontitis, suggesting at least one association between the two pathologies. This group had the highest percentage of severe periodontitis, which means that the more severe periodontitis levels were linked to more advanced forms of atherosclerosis. Conclusions: This research has shown an association between the most severe forms of periodontitis and an increase in the intima-medium thickness. In addition, the increased severity of periodontal disease was associated with the presence of atheroma plaques in a significant number of patients, suggesting at least an association between the two pathologies.